Readiness levels of intern nursing students during the transition to professional practice within the Al Jouf Region in Saudi Arabia - Abeer N. Alruwaili; Majed M. Alruwaili; Normajean Colby (BMC, 2024)
Abstract Background The transition of newly graduated nurses into the workforce is recognized as a complex undertaking and has been examined extensively in the literature. Objective This study aimed to assess the readiness levels of intern nursing students and investigate the factors affecting their transition to professional practice within the Al Jouf region in Saudi Arabia. Methods The study employed a combination of descriptive, correlational, and qualitative methodologies to conduct its investigation. Data were acquired via an online questionnaire that included demographic information, the Nursing Practice Readiness Scale (NPRS), and two open-ended questions. A total of 135 nursing intern students were recruited to participate in the study. Benner's "novice-to-expert" theory of clinical competence was utilized to guide the theoretical underpinning of the study. Results Findings revealed that most intern nursing students (63.7%) exhibited a moderate level of readiness. Furthermore, 70.4% and 55.6% of the students showed moderate readiness in terms of their professional attitudes and patient-centeredness, respectively. More than one-third of the students demonstrated a high level of readiness in the self-regulation domain (36.3%), while a similar proportion indicated a high level of readiness in the domain of collaborative interpersonal relationships (33.3%). The students underscored their reliance on the education system as pivotal in enhancing their preparedness for clinical practice. Conclusion Nursing internship programs contribute to a more comprehensive readiness of nurses for active participation in clinical practice as compared to traditional educational programs.